From Freud’s Woman to Lacan’s Women: Implications in Clinical Practice - Cristiana Cimino (EJP import test, 2015)
Summary: The theme of the feminine has undergone considerable transformations in the field of psychoanalytic formalisation: the author illustrates these in a path that goes from Freud to Lacan. From the Freudian universal woman, all ascribable to structure, Lacan moves on to The women, inhabited by an additional pleasure with respect to the phallic, an Other pleasure, not ascribable to structure. He consigns it to the non-universal register of the one-by-one. In addition to its theoretical significance, this perspective has significant implications for psychoanalytic practice too. On the one hand, it revives the importance of work on castration, Freud’s insurmountable “bedrock,” which Lacan instead turned into a strong point; and on the other, it commits analysts to the feminine singularity of each and every one, obliging them to invent new unique solutions for every subject.
Keywords: Castration; Freud; Lacan; the Feminine